On closure operators and the sieve formula - Dohmen, Klaus (Utilitas Mathematica, 2000)
Let Av v∈v be a finite family of sets. We establish an improved sieve formula for any suitable closure operator on the power set of V, thus generalizing several well-known results from the literature.